IJCM_248A: Visual health related to quality of life and visual acuity in cataract patients advised for surgery: A hospital-based cross-sectional study - Jain Animesh; Rao M Archana; Bhat M Shashank; Soumya; Shrigiri; Shalaka R; Anubha A J (Wolters Kluwer Medknow Publications, 2024)
Background: Vision plays a pivotal role in daily activities, and its impairment, often caused by cataracts, significantly impacts the quality of life. Cataracts, characterized by cloudiness or opacity in the eye lens, contribute significantly to visual impairment, especially in individuals over 60 years. The prevalence of cataract-induced blindness in India is alarmingly high, with 80.1% of blindness and 58% of senile cataract cases attributed to this condition. Objectives: To assess the impact of cataract surgery on the visual health- related quality of life (VHRQoL) among patients. Methodologyology: This hospital-based cross-sectional study was conducted at Government Wenlock Hospital and KMC Mangalore Attavar, hospitals affiliated to Kasturba Medical college, Mangalore. The study included cataract patients, both preoperative and postoperative, excluding those with other eye-related disorders. Non-probability (purposive) sampling was employed, determining a sample size of 60 based on a 95% confidence level and 62% prevalence of cataract. Results: Patients undergoing cataract surgery exhibited notable improvements in general vision, ocular pain, mental health, and near activities. Enhanced role performance, social life, and reduced dependency were observed. Post-operative visual acuity improved, especially for pre-operative values below 6/18. VFQ-J11 revealed significant associations in 4 out of 7 domains, surpassing VFQ-25 (2 out of 12), making VFQ-J11 a preferred tool for assessing pre- operative and post-operative patients. Conclusion: The cataract surgery leads to an overall enhancement in the quality of life for the majority of patients, with a moderate correlation between VHRQoL improvement and visual acuity.